DAKWAH ISLAMIYAH MELALUI MEDIA BAHASA ARAB - Ahmad Taufik (Jurnal khabar: Komunikasi dan Penyiaran Islam, 2020)
Da'wah is a form of religious communication whose main purpose is amar ma'ruf and nahi munkar with the object of preaching, mad'u, both in the form of individuals and groups. Da'i as the perpetrators of da'wah are required to master the da'wah material that will be conveyed to the mad'inya, including the issue of aqeedah, sharia, and morals. As for the sources of propaganda material, the Qur'an and Hadith which are the highest sources of teachings and sources of Islamic law. The existence of Arabic in preaching is so important because both sources of preaching material use Arabic, so that Arabic is the key to opening Islamic knowledge. To study and deepen it also requires mastery of various branches of science such as the Science of Interpretation, Nahwu Science, Bayan Science, Usul Fiqh, and others, which are not far from Arabic. In addition, the original literary books which are the result of thoughts, offerings to the Qur'an and hadith by the scholars of the past written in Arabic, all of which are part of the source of propaganda material that should be known by the preachers . All of this aims to deliver propaganda material from the Qur'an and Hadith in accordance with Islamic law and away from the understanding received by the mad'u in receiving messages delivered by a preacher.